SUSTAINABLE ECOLOGICAL PLANNING STUDY OF SEBERANG FISHERMAN VILLAGE RESIDENTIAL AREA, PALUH KURAU, NORTH SUMATRA PROVINCE - Yusen Effendy; Feby Milanie; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2025)
Seberang Fishermen's Village, Paluh Kurau, Muara Belawan, North Sumatra Province, is an area that functions as a residence and fishing ground. Slum areas, inconsistencies in spatial planning, limited land, irregular buildings with poor quality, high density, disease susceptibility, poor infrastructure, vulnerability to social problems and poverty are the problems facing microorganisms in Seberang Fishermen's Village, Paluh Kurau. This study used qualitative methods with a descriptive approach to provide an assessment of organizational planning strategies, focusing on harmony through the linkages and unity between policies, natural conditions, economics, and socio-cultural aspects, while considering ecological values in line with national development goals. The study concluded that planning focuses on increasing community empowerment, ecological planning, and enhancing the community's social capital structure.